1982
DOI: 10.1042/bj2030277
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cellobiose dehydrogenase in the cellulolytic fungus Sporotrichum (Chrysosporium) thermophile

Abstract: An extracellular enzyme from culture filtrates of Sporotrichum (Chrysosporium) thermophile (A.T.C.C. 42 464) after growth on cellulose or cellobiose was shown to oxidize cellobiose to cellobionic acid in vitro. Lactose and cellodextrins were also efficiently oxidized, but the enzyme was not active against most mono- and di-saccharides. Several redox substances could act as electron acceptors, but molecular oxygen, tetrazolium salts and NAD(P) were not reduced. Activity was stimulated up to 2-fold in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…The absorption spectra of the enzyme indicated the presence of neither a heme nor an FAD group. Since the catalytic properties of the enzyme were similar to those of the first described cellobiose dehydrogenases (13,15)-at that time a term commonly used for the flavin-only enzyme-it also was termed cellobiose dehydrogenase, and it was speculated that it might possibly carry a different cofactor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption spectra of the enzyme indicated the presence of neither a heme nor an FAD group. Since the catalytic properties of the enzyme were similar to those of the first described cellobiose dehydrogenases (13,15)-at that time a term commonly used for the flavin-only enzyme-it also was termed cellobiose dehydrogenase, and it was speculated that it might possibly carry a different cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…Cellobiose dehydrogenase has been isolated and characterized from a variety of white-rot fungi (2,6,21,38,43,53), soft-rot fungi (13,15,20,50,52), and one brown-rot fungus (49). Typically, CDH is a monomeric protein consisting of two domains, one containing a hexacoordinate heme b (14) and one containing a noncovalently bound flavin adenine dinucleotide (FAD) (6,43) or 6-hydroxy FAD (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These properties suggested that the enzyme VOL. 64,2000 PHYSIOLOGY AND ENZYMES OF THERMOPHILIC FUNGI 477…”
Section: Laccasementioning
confidence: 99%
“…CDH activity was reported in cultures of the ascomycetes Thielavia heterothallica (synonyms, Myceliophthora thermophila and Sporotrichum thermophile) (3,4), Chaetomium sp. INBI 2-26(Ϫ) (38), Chaetomium cellulolyticum (10), Neurospora crassa (11), Humicola insolens (32), and Myriococcum thermophilum (14).…”
mentioning
confidence: 99%